PROSPECTS OF ECOLOGIZATION OF THE ECONOMY OF UKRAINE IN THE CONDITIONS OF EUROPEAN INTEGRATION (INNOVATIVE ECONOMY, 2023)
Pecheniuk A.V. PROSPECTS OF ECOLOGIZATION OF THE ECONOMY OF UKRAINE IN THE CONDITIONS OF EUROPEAN INTEGRATIONPurpose. The aim of the article is to substantiate the priority areas of greening of the domestic economy for the realization of Ukraine's desire to become a full member of the European Union.Methodology of research. Appropriate methods and techniques were used in the research process: dialectical – to learn the essence and nature of the process of greening the economy, induction and deduction – to find, systematize and process the necessary information, monographic – to learn the experience of ecological modernization of the economy of European countries, systemic – to substantiate a set of measures on increasing the efficiency of production greening, abstract and logical and generalization - to form conclusions from the conducted research.Findings. The article summarizes the main reasons for the need for ecological modernization of the economies of the world, and indicates the relevance of the problem for Ukraine in the context of integration into the European Union. The main ecological and economic problems of the state's development are revealed, the obstacles to the implementation of the principles of the "green" economy are highlighted, and the consequences of the full-scale military invasion of the Russian Federation for the environment and economy of Ukraine are analysed. The experience of implementing the nature protection component in the economy of the countries of the European Union is summarized. The impossibility of effective greening of the economy before the end of the war, in the conditions of an unstable political situation, a chronic lack of financial resources, and an inappropriate investment climate in the state, was noted.Originality. Work on the adaptation of domestic environmental protection legislation to EU standards, the development and implementation of the state program for the restoration of the environment destroyed by the war was further developed.Practical value. The processes of stimulating the development of the circular economy, the introduction of the service model of customer service, and the focus on decoupling will allow to increase the efficiency of the greening of production processes in Ukraine.Key words: ecologization of the economy, balanced use of nature, European integration, environmental policy, "green" economy, circular economy, ecological modernization, ecological certificates.
Keywords: ecologization of the economy; balanced use of nature; European integration; environmental policy; "green" economy; circular economy; ecological modernization; ecological certificates